A Comparative Study on Corona Virus Pandemic – What do figures indicate? - Alagappan, Annamalai; Venkatachary, Sampath Kumar; Baptist, Leo John; Samikannu, Ravi; Prasad, Jagdish; Immaculate, Anitha (International Review of Management and Marketing, 2020)
Coronavirus disease 2019 (COVID 19) is recognized as one of the most significant outbreak in recent times given the spread across the nations. It has affected over 185 countries across the globe and is still expanding significantly. This paper aims to compare the data on two counts and a detailed descriptive analysis is presented in the paper. Given the threat level and the classification of the disease as a pandemic, an attempt is made to analyse the data based on a linear regression estimation and predict its evolution. The statistical results indicate that the death and the recovery rate are influenced substantially by the facilities available in the form of hospital beds, patient-physician and nurse ratio. Keywords: Corona Virus, Statistical, SARS; MERS JEL Classifications: I0; I1; I2; C0 DOI: https://doi.org/10.32479/irmm.10320